Signs and Symptoms with Men after Hemiplegia: Understanding the needs of men with hemiplegia and implications for clinical practice and research (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Hemiplegia, or paralysis of one side of the body, results from injury or disease (e.g., stroke) and leads to other disabilities. People with hemiplegia have physical limitations in daily activities. This restriction affects their social well-being and can therefore lead to depression. The following is an important discussion of the signs and symptoms of male depression and humanistic attitudes toward hemiplegic men. Important areas of recovery, social support and partnership development are also highlighted. This article aims to enable health and social care providers to better understand the needs of men with hemiplegia. The implications for clinical practice and research are also discussed.